2017
DOI: 10.1038/pcan.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

Lutetium-177-labelled anti-prostate-specific membrane antigen antibody and ligands for the treatment of metastatic castrate-resistant prostate cancer: a systematic review and meta-analysis

Abstract: This review suggests promising early results for the treatment of mCRPC, especially from patients treated with the more recently developed radioligands. Overall, our meta-analysis showed that approximately two-thirds of patients had a biochemical response. Randomised-controlled trials would be necessary to verify its effectiveness against current systemic therapies and create an ideal treatment protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 32 publications
0
68
2
3
Order By: Relevance
“…Our systematic review found a higher response rate for 177 Lu-PSMA RLT than the previous systematic review by Calopedos et al [ 16 ]. The difference may be due to differences in selection of articles.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Our systematic review found a higher response rate for 177 Lu-PSMA RLT than the previous systematic review by Calopedos et al [ 16 ]. The difference may be due to differences in selection of articles.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, our systematic review evaluated the selection of articles with funnel plots, and included boxplots of the frequency of objective remission and overall survival as end-points for effect of the treatment. Anyway, both systematic review supported that 177 Lu-PSMA RLT is effective as treatment of mCRPC [ 16 ]. 177 Lu-PSMA-617 RLT and 177 Lu-PSMA I&T caused a best PSA decline of ≥50% more often and caused less adverse effects than 177 Lu-J591.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10. Lutetium-177-labelled anti-prostate-specific membrane antigen antibody and ligands for the treatment of metastatic castrate-resistant prostate cancer: a systematic review and meta-analysis [11]. This review discusses novel PSMA tracers for imaging and radioimmunotherapy of men with recurrent prostate cancer, now in phase-3 trials.…”
Section: Non-metastatic Castration Resistant Prostate Can-mentioning
confidence: 99%